Merdeka Curriculum Better than K13 Curriculum? Comparative Analysis of Merdeka Curriculum Mathematics Textbooks with the K13 Curriculum - Zahirotul Kamiliyah; Roizatul Faruk (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The latest textbooks from the Merdeka curriculum are only available for the first year, namely 2022 for the first level. However, many people still doubt its effectiveness because the Merdeka curriculum is still in the socialization period. This study wants to dig deeper into the latest curriculum textbooks compared to the previous curriculum. This study was conducted using the comparative method of primary data. The K13 and the Merdeka Curriculum Textbooks were analyzed using textbook standards from the BSNP, which consisted of 4 aspects: Material Content, Material Presentation, Language, and Graphical elements. Then, do the scoring to measure suitability. The study results show that the Merdeka Curriculum textbooks get a higher score than the K13 textbooks as a whole and in every assessment aspect